Faculty support and belonging among international students: Chain mediation of perceived campus climate and self-efficacy - Samadieh, Hadi; Rashidi, Mahsa; Dashtbayazi, Niyayesh; Ghanbari, Zahra (Journal of International Students, 2026)
This study examined how faculty support influences international students’ sense of belonging, with a focus on the mediating roles of perceived campus climate and self-efficacy. A total of 512 international students at four public universities in Iran completed online questionnaires. Using Hayes’ PROCESS Model 6, the results showed that faculty support was positively associated with perceived campus climate, which, in turn, predicted students’ sense of belonging. However, the direct effect of faculty support on belonging and the indirect effect through self-efficacy alone were not significant. Although campus climate was positively associated with self-efficacy, full mediation was not supported. These findings highlight the key role of a supportive campus climate in enhancing international students’ belonging, while self-efficacy plays a less central role. The study emphasizes the importance of institutional and interpersonal factors in promoting socio-emotional integration of international students in higher education.